2009
DOI: 10.1186/1471-244x-9-48
|View full text |Cite
|
Sign up to set email alerts
|

Number of addictive substances used related to increased risk of unnatural death: A combined medico-legal and case-record study

Abstract: Background: Substance use disorders have repeatedly been found to lead to premature death, i.e. drug-related death by disease, fatal intoxications, or trauma (accidents, suicide, undetermined suicide, and homicide). The present study examined the relationship between multi-drug substance use and natural and unnatural death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
1
19
0
4
Order By: Relevance
“…This agreed with results reported in previous studies (15)(16)(17)(18). Aggressiveness and social consequences are interrelated.…”
Section: Associations Of Spu With Mental Social and Physical Factorssupporting
confidence: 83%
See 1 more Smart Citation
“…This agreed with results reported in previous studies (15)(16)(17)(18). Aggressiveness and social consequences are interrelated.…”
Section: Associations Of Spu With Mental Social and Physical Factorssupporting
confidence: 83%
“…Indeed, polydrug use is associated with a unique set of consequences (8), including psychological morbidity/pathology (9)(10)(11), health risk behaviors (12) [e.g., HIV risk-taking (5)], difficulties engaging in drug-abuse therapy (13), and worse outcomes following drug-abuse treatment (14). Moreover, some studies indicated that the abuse of a higher number of substances was associated with more severe health outcomes (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, over the past decade, fatal opioid overdose has emerged as a major public health issue internationally (7). The major cause of deaths related to opioid overdose has shown to be inadvertence (8). The case we present has showed that careless and unaware consumption of poppy capsule is a great danger often resulting with mortality.…”
Section: Discussionmentioning
confidence: 75%
“…Les empoisonnements peuvent être définis par l'exposition d'un individu (par ingestion, inhalation, injection) à une quantité de substance(s) potentiellement dangereuse(s). Ces empoisonnements sont d'origine accidentelle, volontaire ou criminelle et la mort peut être le résultat des effets directs ou indirects, immédiats ou chroniques de l'exposition [1]. Ainsi, les xé-nobiotiques peuvent être directement responsables du décès, mais peuvent aussi être associés à d'autres circonstances morbides telles que la noyade, la défenestration, l'immolation, le polytraumatisme routier [2,3].…”
Section: Introductionunclassified
“…Ainsi, les xé-nobiotiques peuvent être directement responsables du décès, mais peuvent aussi être associés à d'autres circonstances morbides telles que la noyade, la défenestration, l'immolation, le polytraumatisme routier [2,3]. Dans ce sens, le décès est qualifié d'origine toxique lorsque le ou les xénobiotiques identifiés sont présents en concentration toxique, voire létale et ceci malgré une causalité secondaire et indirecte de cette toxicité [1,4]. Les décès d'origine toxique sont recensés dans différentes études épidémiologiques, notamment celles effectuées par le CépiDc (organisme affilié à l'INSERM).…”
Section: Introductionunclassified